Establishing an assessment framework for the risk of dinoflagellate HABs based on cyst-mapping of marine sediments - Pan, Suzhi; Shang, Lixia; Liu, Xiaohan; Liu, Yuyang; Tao, Zhe; Deng, Yunyan; Chai, Zhaoyang; Tang, Yingzhong (Journal of oceanology and limnology, 2025)
Harmful algal blooms (HABs) of dinoflagellates pose significant threats to aquaculture, marine ecosystems, and human health. While resting cysts have been well known for their vital roles in initiating HABs of dinoflagellates, mapping results of the cyst abundance and distribution in marine sediments have been also well documented to be a highly valuable predictor, and thus can be used as a basis to assess the risk of HABs. We attempted to establish a framework for the risk assessment of dinoflagellate HABs based mainly on cyst-mapping of marine sediments and a case application of it to the risk assessment of HABs in the Yellow Sea. In the framework, firstly, the targeted marine area subjected to the assessment was determined and gridded into different assessment units according to their geography, administration, and ecological or economic function. Secondly, the dinoflagellate cyst abundance from the surface sediment, HABs records, and the monitoring results of vegetative cells for all or particular species of concern were collected experimentally or by literature search, as three main indicators scored and weighted respectively with different values. The scoring and weighting process was based on scientific reasoning and empirical consideration as detailed in the text. Thirdly, the risk of HABs occurrences for all or any particular species of concern at each site was ranked with five levels according to the calculated risk values. Finally, the final evaluation results were presented with tables, matrix diagrams, and color-coded textual annotations on nautical charts. As a case application, we performed a risk assessment for HABs of target species in the Yellow Sea, which warned high risks of HABs for Karlodinium veneficum, Gymnodinium catenatum , and others. This assessment framework provides a practical and testable tool for all involved stakeholders, and subject to improvement along with the advancement of ecology of HABs.